Coastal Reclamation in Ambon City for the Society in the Perspective of Environmental Law - Victor Juzuf Sedubun (Universitas Airlangga, 2023)
AbstractCoastal reclamation in several villages in the deep bay of Ambon City has an impact on the environment and causes rejection from the society. Reclamation is a challenge for the Ambon City Government in making efforts to manage coastal areas, in a sustainable manner. In principle, reclamation is a method to restore environmental functions that have been damaged. The issues in this reseach are: what is the impact of reclamation on the people of Ambon City in terms of environmental law? The aim of this research to analyze the impact of reclamation on the people of Ambon City in terms of environmental law. This research uses a normative research with statute approach and conceptual approach. The inventory was conducted towards primary and secondary legal materials and they were then classified. The result of the analysis indicates the arguments to suggest some prescriptions to solve the analyzed problem. Reclamation on the coast of Teluk Ambon and Teluk Dalam Ambon has an impact on the destruction that occurs in mangrove forests, sedimentation, rob floods in certain areas. Supervision by the Ambon City Government has not been optimal to prevent further damage. Management and sustainable use of the environment by humans is very important to ensure the availability of a good environment for future generations.